Analisis Ekonomi Budidaya Madu Kelulut (Trigona Itama) di Desa Layuh Kecamatan Batu Benawa Kabupaten Hulu Sungai Selatan (HST) - Hafizah, Nirma; Yunani , Ahmad (PPJP ULM, 2022)
The objectives of this study were (1) to analyze the feasibility of cultivating kelulut honey in Layuh village, Batu Benawa sub-district, Hulu Sungai Tengah regency (HST); (2) to Analyze the economic potential of kelulut honey cultivation in Layuh Village, Batu Benawa District, Hulu Sungai Tengah Regency (HST); (3) To find out the strategy for developing kelulut honey cultivation in Layuh Village, Batu Benawa District, Hulu Sungai Tengah Regency (HST). This research uses descriptive quantitative research. The location of this research is in Layuh Village, Batu Benawa District, Hulu Sungai Tengah Regency (HST). This study uses a feasibility analysis and a SWOT analysis. The results obtained in this study show that the cultivation of kelulut honey (Trigona Itama), which is managed by the local community, can be run and is feasible to manage. The development strategy in this SOWT business analysis must overcome existing weaknesses by taking advantage of emerging opportunities.